Free Vibration Analysis of Bulkhead-Stiffened Functionally Graded Open Shell Using a Meshless Method - Songhun Kwak; Kwanghun Kim; Kyongjin Pang; Sok Kim; Pyol Kim (Shock and Vibration)
This paper focuses on the free vibration analysis of bulkhead-stiffened functionally graded open shell (FGOS) by means of the first-order shear deformation theory (FSDT) and the meshless strong form method. The bulkhead-stiffened FGOS is decomposed into several segments without bulkhead, and the equations of motion and boundary conditions for each segment are discretized by meshless strong form method, and the displacement components are approximated using meshfree Legendre–RIPM shape function using the combined basis of multi-quadrics (MQ) radial function and Legendre polynomials. The continuous conditions of displacement are applied at the interfaces between segments. The boundary and continuous conditions are enforced by using the artificial spring technique. The accuracy and reliability of the current method are validated by comparing the present results with those of the kinds of literature and the finite element program ABAQUS. The effects of some geometrical parameters and boundary conditions on the natural frequencies of bulkhead-stiffened FGOS are investigated through numerical examples, which may serve as benchmark data.